An Intervention-Based Active-Learning Strategy To Enhance Student Performance in Mathematics - Gaganpreet Sidhu; Seshasai Srinivasan (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2018)
Experiments were performed to study the effect of integrating an intervention strategy on student learning in an active learning environment in three different undergraduate mathematics courses. In these pedagogical experiments, the learning was measured via several subjective tests and the overall final grade for each course. For each course the comparison was made between two sections, one receiving the material via traditional instruction (control section) and the second receiving the material via instruction based on the active learning strategy (experimental section). It was found that students taught using the latter approach performed significantly better in the tests and exams, reflecting a good understanding of the material.